2015
DOI: 10.4315/0362-028x.jfp-14-405
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Vibrio parahaemolyticus, Vibrio cholerae, and Vibrio vulnificus in the Aquacultural Environments of Taiwan

Abstract: The occurrence of Vibrio parahaemolyticus, Vibrio vulnificus, and Vibrio cholerae in a total of 72 samples from six aquaculture ponds for groupers, milk fish, and tilapia in southern Taiwan was examined by the membrane filtration and colony hybridization method. The halophilic V. parahaemolyticus was only recovered in seawater ponds, with a high isolation frequency of 86.1% and a mean density of 2.6 log CFU/g. V. cholerae was found in both the seawater and freshwater ponds but preferentially in freshwater pond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
3
12
1
Order By: Relevance
“…Several studies have reported conflicting results regarding the correlations between the abundance of V. parahaemolyticus and salinity. Some of these studies have found a correlation between salinity and abundance of V. parahaemolyticus [65][66][67][68], while others have not [58,64,[69][70][71][72]. Thus, the insignificance of salinity on the abundance of V. parahaemolyticus identified in this study cannot be generalized.…”
Section: Plos Onecontrasting
confidence: 66%
“…Several studies have reported conflicting results regarding the correlations between the abundance of V. parahaemolyticus and salinity. Some of these studies have found a correlation between salinity and abundance of V. parahaemolyticus [65][66][67][68], while others have not [58,64,[69][70][71][72]. Thus, the insignificance of salinity on the abundance of V. parahaemolyticus identified in this study cannot be generalized.…”
Section: Plos Onecontrasting
confidence: 66%
“…Therefore, if the population density of these microbial groups increases considerably, fish health can be threatened, affecting fish farming in the zone. Furthermore, diseases produced by Vibrio spp can be generated due to excessive feeding, high fish density, increased number of microorganisms, such as coliforms and heterotrophs, as well as the loss of water quality due to excessive nutrients [32].…”
Section: Coliformsmentioning
confidence: 99%
“…Clinical characteristics include watery diarrhea, abdominal cramps, nausea, and fever ( 3 , 4 ). However, V. parahaemolyticus infections are not exclusive to humans and have recently been demonstrated to be a major source of disease in aquaculture production ( 5 , 6 ). Therefore, monitoring of this pathogenic Vibrio species in aquaculture environments is important for both the aquaculture industry and human health.…”
Section: Genome Announcementmentioning
confidence: 99%